Catalytic Hydrodeoxygenation of Lignin-Derived Feedstock Into Arenes and Phenolics - Jing, Yaxuan; Wang, Yanqin (Frontiers in Chemical Engineering, 2020)
lignin, as the only most abundant aromatic source in nature, shows great potential to address environmental and energy problems. Hydrodeoxygenation (HDO) as a useful way of converting lignin and its-derived compounds into value-added aromatic chemicals and fuels is able to transform the vision “fueling the future” into reality, thus garnering considerable attention in the past decade. The purpose of this minireview is to specifically address the removal of phenolic hydroxyl groups and/or methoxy groups within lignin, mainly focusing on the core questions and challenges of catalytic systems. Our own insights into future studies and recommendations for future research in this promising field are also provided.